“Post-Anthropocentrism” in Animal Philosophy and Ethics: The Disparity of the Prefix “Post” - Aigner, Andreas; Pieper, Karl; Grimm, Herwig (Humanimalia, 2016)
The field of post-anthropocentrism in current animal philosophy and related disciplines is structured by heterogeneous concepts of anthropocentrism on the one hand and different usages of the prefix ‘post’ on the other. This paper expounds different perspectives on anthropocentrism, while additionally focusing on the possibilities of its overcoming: on how anthropocentrism is problematized rather than on what is problematized. Two different positions are used as examples: humanist post-anthropocentrism, as advocated by Gary Steiner, and post-humanism, as advocated by Cary Wolfe in reference to Jacques Derrida’s deconstruction. In conclusion, the notion of ‘excess’ is analysed to illustrate the structural differences regarding a crucial term for both positions.